Blount Disease and Obstructive Sleep Apnea: An Under-recognized Association?. Issue 10 (November 2020) - Jardaly, Achraf; McGwin, Gerald; Gilbert, Shawn R.
Abstract : Background: Obesity is strongly associated with both Blount disease and obstructive sleep apnea (OSA). Obesity increases risks for anesthetic and postoperative complications, and OSA can further exacerbate these risks. Since children with Blount disease might have both conditions, we sought to determine the perioperative complications and the prevalence of OSA among these children. Methods: Patients younger than 18 years undergoing corrective surgery for Blount disease were identified from 2 sources as follows: a retrospective review of records at a single institution and querying of the Kids' Inpatient Database, a nationally representative database. Results: At our institution, the prevalence of OSA among patients surgically treated for Blount disease was 23% (42/184). Blount patients were obese (100%), and predominately African American (89%), and male (68%). Patients were treated for OSA before surgery, and 2 patients (1%) had postoperative hypoxemia. In contrast, of 1059 cases of Blount disease from the Kids' Inpatient Database, 3% were diagnosed with OSA. In total, 4.4% of all the Blount children experienced complications, including hypoxemia, respiratory insufficiency, atelectasis, and arrhythmias. Complications were associated with 4.3 additional days of hospitalization ( P <0.0001) and 39% additional hospital charges ( P =0.002). Conclusions: Data from the national database showed a low rate of OSA prevalence but high respiratory and OSA-associated complications, perhaps indicating that OSA may be underdiagnosed in children with Blount disease. Affected patients, especially ones with untreated OSA, sustain increased surgical morbidity. A high index of suspicion and preoperative planning helps alleviate the burden of OSA among these patients. Level of Evidence: Level III—case-control study. Abstract : Supplemental Digital Content is available in the text.